2016
DOI: 10.1016/s2352-3026(16)30049-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of salvage autologous stem-cell transplantation on overall survival in patients with relapsed multiple myeloma (final results from BSBMT/UKMF Myeloma X Relapse [Intensive]): a randomised, open-label, phase 3 trial

Abstract: Cancer Research UK, Janssen-Cilag, and Chugai Pharma UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 33 publications
4
108
0
Order By: Relevance
“…Their findings confirm the results from many other similar retrospective and prospective studies conducted in Europe and the USA which demonstrate that salvage ASCT in relapsed MM is feasible [2, 3]. They demonstrate that patients enjoying a longer relapse-free survival after their first ASCT appear to do the best in terms of survival postsalvage ASCT.…”
supporting
confidence: 87%
“…Their findings confirm the results from many other similar retrospective and prospective studies conducted in Europe and the USA which demonstrate that salvage ASCT in relapsed MM is feasible [2, 3]. They demonstrate that patients enjoying a longer relapse-free survival after their first ASCT appear to do the best in terms of survival postsalvage ASCT.…”
supporting
confidence: 87%
“…89 Moreover, overall survival for patients randomized to a second ASCT was higher than for controls (67 months vs 52 months; P =.0169). 153 Given that these patients did not receive any maintenance therapy after their second ASCT, the duration of the response is acceptable. There is increasing evidence of benefit of ASCT even in the older population, and therefore patients should be referred for evaluation to a transplant center because ASCT can have a positive effect on survival in this population.…”
Section: Therapy For Patients In First Relapsementioning
confidence: 99%
“…Prognostic factors associated with prolonged PFS in these reports included quality and duration of response to the first high‐dose therapy (ASCT1), the number of lines of therapy before salvage ASCT (ASCT2), younger age, and lower β‐2‐microglobuline at diagnosis . The BSBMT/UKMF myeloma X trial for relapsed MM patients represents so far the only prospective study that compared salvage ASCT with continued conventional chemotherapy (weekly cyclophosphamide), and the trial reported a significant benefit for PFS and OS for the ASCT arm . However, more potent alternatives to salvage ASCT have become available, and their direct comparison to salvage ASCT remains untested.…”
Section: Introductionmentioning
confidence: 99%